Boycotting Japan: Explaining Divergence in Chinese and South Korean Economic Backlash. (December 2019) - Vekasi, Kristin; Nam, Jiwon
Abstract: Japan has a 'cold politics, hot economics' relationship with both China and South Korea where political relations are tense and business overall flourishes. Despite the similarities, the political mobilisation of consumers in response to Japanese business interests diverge: event, trade and tourism data show that South Koreans are less likely to link economic interests with their political grievances with Japan compared to their Chinese counterparts even though the sources of the tensions are largely parallel. The divergence arises from different ways economic globalisation has shaped national identity. In China, economic globalisation has strengthened a nativist identity with strong anti-foreign components. Korean national identity has been formed by economic integration and interdependence. While strong national identity and anti-foreign elements exist, they are delinked from economic interests. Survey and event data from South Korea and China show that the variation in consumer politics is driven by attitudinal differences in the population that is strongly anti-Japanese. Social media data shows how citizens link or delink politics and business to mobilise for collective action and provide qualitative evidence that how identities interact with globalisation explain country-level variation.